Functional rare variants influence the clinical response to anti-TNF therapy in Crohn's disease. (September 2019) - Chaparro, María; Aterido, Adrià; Guerra, Iván; Iborra, Marisa; Cabriada, Jose Luis; Bujanda, Luis; Taxonera, Carlos; García-Sánchez, Valle; Marín-Jiménez, Ignacio; Barreiro-de Acosta, Manuel; Vera, Isabel; Martín-Arranz, Maria Dolores; et al.
Background: The effect of low-frequency functional variation on anti-tumor necrosis factor alpha (TNF) response in Crohn's disease (CD) patients remains unexplored. The objective of this study was to investigate the impact of functional rare variants in clinical response to anti-TNF therapy in CD. Methods: CD anti-TNF naïve patients starting anti-TNF treatment due to active disease [Crohn's Disease Activity Index (CDAI > 150)] were included. The whole genome was sequenced using the Illumina Hiseq4000 platform. Clinical response was defined as a CDAI score <150 at week 14 of anti-TNF treatment. Low-frequency variants were annotated and classified according to their damaging potential. The whole genome of CD patients was screened to identify homozygous loss-of-function (LoF) variants. The TNF signaling pathway was tested for overabundance of damaging variants using the SKAT-O method. Functional implication of the associated rare variation was evaluated using cell-type epigenetic enrichment analyses. Results: A total of 41 consecutive CD patients were included; 3250 functional rare variants were identified (2682 damaging and 568 LoF variants). Two homozygous LoF mutations were found in HLA-B and HLA-DRB1 genes associated with lack of response and remission, respectively. Genome-wide LoF variants were enriched in epigenetic marks specific for the gastrointestinal tissue (colon, p = 4.11e–4; duodenum, p = 0.011). The burden of damaging variation in the TNF signaling pathway was associated with response to anti-TNF therapy ( p = 0.016); damaging variants were enriched in epigenetic marks from CD8 + ( p = 6.01e–4) and CD4+ ( p = 0.032) T cells. Conclusions: Functional rare variants are involved in the response to anti-TNF therapy in CD. Cell-type enrichment analysis suggests that the gut mucosa and CD8 + T cells are the main mediators of this response.